Integrasi Agama dan Sains dalam Perspektif Ismail Raji Al-Faruqi - Sandi, Radila; Dewi, Eva; M, Amril (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2023)
The purpose of this research is to find out the thoughts of Ismail Raji Al-Faruqi related to the Integration of religion and Science. This research method uses descriptive qualitative using a literature study approach (Library Research). The results of this study show that Ismail Raji al-Faruqi (1921-1986) was born in Jaffa, a city on the southern coast of Palestine, (now in the territory of Israel). Al-Faruqi's monotheistic worldview is actually based on the desire to renew and refresh the initial ideational insights of the Salafiyah movement reformers, such as: Muhammad ibnu Abdul Wahab, Muhammad Idris As-Sanusi, Hasan Albana and so on. The Islamization of science is done by synthesizing Islam and modern science. This process must go through twelve stages, namely: (1) Mastery of modern scientific disciplines (2) Survey of disciplines. (3) Mastering the treasures of Islam, (4) If anthologies have been prepared, the treasures of Islamic thought must be analyzed from the perspective of relevant contemporary problems. (5) Determination of specific relevance for each discipline. (6) Critical appraisal of the modern discipline. (7) Critical appraisal of the Islamic treasury (8) Survey of the problems facing Muslims. (9) Survey of the problems facing humanity. (10) Creative analysis and synthesis. (11) Recasting modern disciplines into an Islamic framework. (12) Dissemination of the Islamicized knowledge.